A simple method to disentangle nanoparticle optical properties by darkfield microspectroscopy. Issue 11 (28th July 2014) - Gnerucci, Alessio; Ratto, Fulvio; Centi, Sonia; Conti, Antonio; Pini, Roberto; Fusi, Franco; Romano, Giovanni
ABSTRACT We present a darkfield optical microspectroscopy technique devoted to the disentangled measurement of the absorption and scattering cross sections of nanoparticle (NP) samples with variable concentration. The robustness of the method, including the needed instrumental calibrations, is examined in detail by analyzing and quantifying the major sources of statistic and systematic errors. As an exemplary case, results are presented on a gold NP colloid. The technique takes advantage of a simple inverted microscope, coupled with a spectrograph and equipped with a darkfield condenser and a variable numerical aperture objective to obtain spectra either in darkfield or brightfield optical configurations. By adopting the Lambert–Beer (LB) equation modeling, we were able to disentangle and measure with a single setup the absorption, scattering, and extinction coefficients of the same sample by combining three spectra, obtained by opportunely varying the objective numerical aperture. Typical plasmonic resonances were recognized at approximately 520 and 750 nm. Optical coefficients were measured as a function of particle number density (0.04–3.94 µm−3, corresponding to 40 µM–4 mM nominal Au concentration) and good linearity was verified up to ∼1.5 µm−3 (∼1 mM Au). Moreover, extinction and scattering cross sections were quantified and the validity of the LB approximation was reviewed. Besides its applications to plasmonic NPs, this method may be appropriate for any colloid, provided there exists a characteristic spectral feature in the ultraviolet‐visible‐near infrared range. This technique may be exploited to localize NPs in biological samples. Microsc. Res. Tech. 77:886–895, 2014. © 2014 Wiley Periodicals, Inc.